Analysis of the Relationship between Electricity Subsidies and Non-Subsidies on Household Electricity Consumption (Case Study: Badung Regency) - Vidi, Buana; Saraswaty, Amrita Nugraheni (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
In 2020 the government implemented a full electricity subsidy policy for customers with 450 VA and 900 VA power capacity across Indonesia. This policy was introduced to assist underprivileged communities in facing the COVID-19 pandemic. Badung Regency is one of the regions in Indonesia with rapidly increasing electricity consumption. This study examines the relationship between household electricity subsidies and household electricity consumption, household income, and power capacity, while also investigating the occurrence of moral hazard among household customers in Badung Regency. The research employs a quantitative approach using primary data. Data was collected from a sample of 100 households. The study utilizes logistic regression analysis techniques. The results show that subsidies, household income, and power capacity have a positive and significant impact on electricity consumption, and there is a 24% occurrence of moral hazard among household customers in Badung Regency. The government should evaluate the implementation of electricity subsidy policies to assess their effectiveness and reduce the potential for moral hazard.